Overview of Kidney Stones and the Potential of Natural Compounds for the Treatment - Huynh Hong Phien; Tran Thanh Men (Research Highlights in Disease and Health Research Vol. 1, 2023)
Kidney stones are a common disease worldwide that can cause different adverse effects on the quality of human life, especially for those suffering from it. Numerous studies have been done to find herbal remedies to support and treat kidney stones. Medicinal plants have the ability to synthesize secondary compounds with good biological activity. This book chapter will give an overview of different types of kidney stones and summarize the research works on natural compounds that are effective in the treatment of kidney stones.